Does a Journal Have an Ethical Monitoring Duty? - Porcino, PhD, HSI, Antony (International Journal of Therapeutic Massage & Bodywork, 2016)
Research and ethics are inseparable. Based on abhorrent research abuses under the cloak of scientific enquiry, development of the process for the ethical overview of research on/with humans was undertaken. By the end of the twentieth century, sufficient and extensive local and international principles, guidelines, legislations, and treaties about research on humans were in place, with all human-based research requiring review by independent research ethics committees (RECs). With so much established knowledge and legislation about the ethical management of the research process and REC oversight, is there a role for journal editorial boards in ethical oversight? Recommendations from the International Committee of Medical Journal Editors, the basis of the editorial policies of the IJTMB, include the requirement that research must be approved by an REC, and documentation of that review should be included in each article. Thus, as a minimum, journals must ensure that any research submitted for publication has had appropriate ethical review. But journals receive manuscripts after research is done. Journals, therefore, have a duty to ensure that received manuscripts meet expected standards for the publication of research and, for nonresearch situations, that appropriate protections of the research participants were in place even though REC review was not involved.